Aspectos sócio-econômico-ambiental do processo de extração do caulim no município de Junco do Seridó-PB - Silva, Dilsom Barros da (2011)
The paper entitled "Socio-Economic and Environmental Process Extraction of Kaolin in the Municipality of Junco do Seridó/PB" is a guided study on the extraction of kaolin in the municipality of Junco do Seridó/PB, which is the largest production center of this mineral in the state Paraíba. This activity is the basis of an extensive and complex supply chains that clay mineral widely used in industry, ceramics, refractories, rubber, paper and paint systems. The extraction of mineral resources is the main source of jobs and income for local people. Currently, about eight hundred men work in mines kaolin, risking their lives in the face of imminent dangers and risks of landslides and still subject to a daily wage of only thirty dollars. Other features consist of the use of tools craft inefficient production, lack of appropriate mining techniques, the expenditure of physical effort in excess, beyond the dismissal of personal protective equipment, even aware of the dangers of underground excavations. Workers are exposed to health hazards and even cases of fatal accidents inside the mines. In most cases, workers are relegated to the margins of legality and informality. To address the socio-economic-environmental process of extracting the kaolin in the municipality of Junco do Seridó/PB. Emphasized that the working conditions of miners in the extractive areas relating them to the sustainability indicators. To set the characterization of aspects, interviews with professionals in the areas of health, education, social class and cooperative. As a result, site visits were conducted to investigate the facilities and working conditions during the extraction process. This activity was characterized as being unsustainable for most of the indicators of sustainability. In light of this concept was performed to analyze the data collected during this study. Based on the Socio-Economic and Environmental extraction of kaolin indicated in this study showed the need for a scientific and technical contribution, planning and strategic management, public policy, training for operation and efficient organization in cooperatives to ensure this type of extraction a sustainable supply chain Junco do Seridó/PB.